FORMULATION AND EVALUATION OF SUSTAINED RELEASE MATRIX TABLETS OF LEVOSULPIRIDE BY USING NATURAL POLYMER - S, SHANMUGAM; R, Babu; S, Satheeshkumar; P, Shanmugasundaram (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the present study was to develop sustained release matrix tablets of levosulpiride by using natural polymers. Method: The tablets were prepared with different ratios of Chitosan, Xanthan gum and Guar gum by wet granulation technique. The solubility study of the levosulpiride was conducted to select a suitable dissolution media for in vitro drug release studies. Results: Fourier transform infrared (FTIR) study revealed no considerable changes in IR peak of levosulpiride and hence no interaction between drug and the excipients. DSC thermograms showed that no drug interaction occurred during the manufacturing process. In vitro dissolution study was carried out for all the formulation and the results compared with marketed sustained release tablet. The drug release from matrix tablets was found to decrease with increase in polymer ratio of Chitosan, Xanthan gum and Guar gum. Conclusion: Formulation LF3 exhibited almost similar drug release profile in dissolution media as that of marketed tablets. From the results of dissolution data fitted to various drug release kinetic equations, it was observed that highest correlation was found for First order, Higuchi's and Korsmeyer equation, which indicate that the drug release occurred via diffusion mechanism. Â Â Â Â